Performing under pressure - Crust, L.; Karageorghis, C.; Lane, A. (Peak Performance, 2007)
Psychology: A throwback to 2004 where one sport psychologist offered his damning verdict on the British Olympic swimming team`s failures Competition Anxiety: The nature of anxiety and its symptoms are explored, with techniques provided to control this anxiety and re-channel it Self-confidence: The importance of selfconfidence in sport is emphasised, with theories and exercises included on how to boost it Mental Strength: Through tennis, a guide to utilising mental strength during competition is illustrated, dealing with both internal and external factors